(untitled) (Altre Modernità, 2020)
The idea that storytelling is a fully cognitive behaviour and a typical attitude of the Homo sapiens species is equally shared by Cognitive Sciences, Psychoanalysis, Literary Theory, Neuroscience, Medical Research and clinical practice. The narration of a trauma or a condition of hardship is commonly considered to be a necessary and healthy practice not only for the narrators but also for the recipients. But what happens when words cannot properly tell the story? When language, certainly not the first nor the only one of our many ways of representing the world, fails and needs to turn to the body or other arts −such as, for example, drawing and theater − to express the magma of emotions otherwise inexpressible?This is what happens in the Atelier dell’Errore, a creative atelier founded in 2002 by the visual artist Luca Santiago Mora as a supplementary service to the clinical activity of the Neuropsychiatry of Reggio Emilia. In the Atelier, teenagers with serious cognitive disabilities tell their stories through drawings, and, more recently, through theatrical performances, that are a remediation and rewriting of the original visual artworks. This paper describes and analyzes this experience of emotional expression, with particular attention to the ways in which the artists and their guide translated their stories and passions from the drawings to the theatrical scene.